Internal Capabilities and State Financial Policy in Advancing Green Banking Practices in Indonesia For SDGs - Alfarizi, Muhammad (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2025)
Amid growing global pressure for sustainability, the banking sector faces increasing demands to adopt environmentally friendly practices through the concept of green banking. This study addresses a gap in the literature by specifically analyzing how internal capabilities and state financial policies drive the adoption of green banking practices in state-owned banks in Indonesia. By integrating the Diffusion of Innovation (DOI) and Resource-Based View (RBV) frameworks, the study offers a novel perspective on sustainability adoption in the banking sector of a developing country. Data were collected through a Likert-scale survey of 274 employees from Indonesian state-owned banks and analyzed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The findings reveal that relative advantage, compatibility, and organizational support are key internal factors driving green banking adoption. Externally, human resource quality, regulatory pressure, sustainable financial policies, and global business dynamics further enhance the adoption process. The results also show that green banking implementation significantly improves Triple Bottom Line (TBL) performance, including operational efficiency and environmental risk reduction. This study highlights the importance of synergy between strengthening internal bank capacities and fiscal policy support—such as tax incentives from the Ministry of Finance—in fostering a sustainable financial ecosystem in Indonesia.